LEGAL REVIEW OF THE LEGALITY OF MARRIAGE AGREEMENTS OF BROUGHT PROPERTY AND GONO GINI PROPERTY TO REALIZE WELFARE FROM A POSISTIVE LEGAL PERSPECTIVE IN INDONESIA - Suwarlan , Suwarlan; Andoko , Andoko; Azhali Siregar (International Journal of Synergy in Law, Criminal, and Justice, 2025)
A marriage agreement is a legal instrument that provides certainty and protection for a husband and wife in regulating the ownership and division of assets, both assets brought into the marriage and joint assets. In practice, disputes regarding assets in a marriage often arise, especially in cases of divorce and inheritance. Positive Indonesian law has regulated the mechanism of a marriage agreement in Law Number 1 of 1974 concerning Marriage, the Civil Code (KUHPerdata), and the Compilation of Islamic Law (KHI). This agreement allows couples to avoid the automatic mixing of assets and regulate their ownership more clearly. In addition to being regulated in positive law, marriage agreements are also based on the principles of contracts in Islam, which emphasize the importance of justice and protection of the rights of couples in marriage. The principle of maqashid sharia, especially hifzh al-mal (protection of property), is the basis for recognizing this agreement as an effort to maintain the welfare and avoid disputes in the future. Constitutional Court Decision Number 69/PUU-XIII/2015 has provided flexibility for couples by allowing marriage agreements to be made not only before but also during the marriage, thus further strengthening legal protection of the rights of couples. However, the implementation of marriage agreements still faces challenges, especially in administrative aspects and the lack of public understanding of the urgency of this agreement. Therefore, wider socialization and harmonization of regulations are needed so that marriage agreements can function effectively in providing legal certainty and justice for married couples in Indonesia. Thus, marriage agreements can be a solution to prevent conflict and maintain household welfare in the future.